Demographic and Health-related Risk Factors of Subclinical Vitamin A Deficiency in Ethiopia - Demissie, Tsegaye; Ali, Ahmed; Mekonnen, Yared; Haider, Jemal; Umeta, Melaku (Journal of Health, Population and Nutrition, 2009)
The study was conducted to determine the demographic and health-related risk factors of subclinical vitamin A deficiency in Ethiopia. Blood samples were collected from 996 children in 210 clusters across the nation for analysis of serum retinol. Interviews were conducted with the respective mothers of the 996 children on presumed risk factors of vitamin A deficiency. A higher subclinical vitamin A deficiency was associated with: not receiving vitamin A supplement over the year, having been ill during the two weeks preceding the survey, no or incomplete vaccination, belonging to a mother with high parity, and low levels of awareness of vitamin A. Moreover, being from Muslim household was strongly associated with higher levels of subclinical vitamin A deficiency. Among the risk factors identified, low levels of vaccination, high parity, and low levels of maternal awareness of vitamin A contributed to higher risks of vitamin A deficiency among Muslim children. The findings underscore the need for creation of strengthened awareness of family planning and importance of vitamin A, promotion of vaccination and child health, intensification of vitamin A supplementation, and in-depth investigation on factors contributing to increased vulnerability of Muslim children. J Health Popul Nutr 2009 Oct; 27(5):666-673